Neandertal subsistence strategies during the Quina Mousterian at Roc de Marsal (France). (17th March 2017) - Castel, Jean-Christophe; Discamps, Emmanuel; Soulier, Marie-Cécile; Sandgathe, Dennis; Dibble, Harold L.; McPherron, Shannon J.P.; Goldberg, Paul; Turq, Alain
Abstract: Recent excavations at the cave site of Roc de Marsal (in the Dordogne region of SW France) have yielded several Mousterian assemblages rich in well-preserved faunal remains. The Layer 4 faunal assemblage, associated with a rich Quina Mousterian occupation, provides an opportunity to investigate Neandertal prey selection, transport decisions and reindeer carcass processing strategies. One of the most striking characteristics of the Roc de Marsal Layer 4 faunal assemblage is an apparent lack of spongy parts that cannot be explained by taphonomic processes or carnivore activities. Limb elements were selectively transported to the site, where they underwent considerable further processing, resulting in a notably high degree of fragmentation of almost all elements. Comparison of reindeer carcass processing strategies employed by Neandertals during the Quina Mousterian with those identified for the later periods of the Upper Palaeolithic gives rise to some unexpected interpretations of Neandertal consumption behaviours. We show that this kind of intensive fragmentation is associated with bone grease rendering in ethnographic and Upper Palaeolithic contexts, in most such cases with the aid of fire. However, evidence of fire is remarkably scarce in Roc de Marsal Layer 4. Layer 4 could reflect a systematic Neandertal practice of sucking and chewing on the spongy portions of bones in order to extract as much of the highly nutritious bone grease as possible. Additionally, Roc de Marsal Layer 4 shows examples of use of animal resources for non-alimentary purposes by Neandertals. The abundance of cutmarks on the anterior surfaces of reindeer metapodials seems to indicate the acquisition of tendons, and bones were frequently used as retouchers.